PERAN PENDIDIKAN ISLAM TERHADAP PENCEGAHAN KORUPSI - Khairuddin Hasan (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Corruption is one of the most crucial problems that continues to whack Indonesia. Corruption has penetrated almost all sectors of state life. The community also became the most suffering victim. Although corruption eradication continues to be carried out, the community seems pessimistic about its success. Almost every day, law enforcers take action, both from arresting to court proceedings. On the one hand, it is evidence that corruption eradication continues. But on the other hand, it is also an indication that corruption has become a latent threat that seems to never end. To overcome the threatening effects of this corruption, the state also takes precautionary action in addition to eradication. Eradication actions take the downstream section, which is after the act of corruption is indicated. Whereas precautionary actions take the upstream section, which is to anticipate for the presence of new corruptors in the future. The role of Islamic education in Indonesia is in the upstream section. Islamic education has had a major contribution to the nation since long before the independence day up to these days. Islamic education often turns up as one of the solutions to national problems. When the threat of corruption hits, Islamic education is again demanded to show its role.